2002
DOI: 10.1051/0004-6361:20021435
|View full text |Cite
|
Sign up to set email alerts
|

Two X-ray bright cataclysmic variables with unusual activities: GZ Cnc and NSV 10934

Abstract: Abstract. We report on a discovery of unexpected activities in two X-ray bright dwarf novae. GZ Cnc showed an anomalous clustering of outbursts in 2002, in contrast to a low outburst frequency in the past record. The activity resembles an increased activity seen in some intermediate polars or candidates. We identified NSV 10934, X-ray selected high-amplitude variable star, as a dwarf nova with unusually rapid decline. The outburst characteristics make NSV 10934 a twin of recently discovered intermediate polar … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 18 publications
3
25
0
Order By: Relevance
“…6 in Patterson 1984). As noted by Kato et al (2002), He II appears to be somewhat stronger than in most dwarf novae, and especially those with a short orbital period.…”
Section: Properties Of the Average Spectramentioning
confidence: 71%
See 3 more Smart Citations
“…6 in Patterson 1984). As noted by Kato et al (2002), He II appears to be somewhat stronger than in most dwarf novae, and especially those with a short orbital period.…”
Section: Properties Of the Average Spectramentioning
confidence: 71%
“…This is a region which is sparsely populated, especially by dwarf novae, and it is therefore of particular interest to determine the CV subtype of the system. Kato et al (2002; hereafter K2002) studied the long-term behaviour, and found a similarity to those of intermediate polars (IPs) in that the outburst distribution appeared to be "clustered". Specifically the authors mention the detection of four outbursts within two months in 2002, while the only known outburst before that date has been recorded at the end of 2000.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…References: (1) Araujo-Betancor et al (2005a); (2) Jiang et al (2000); (3) Nogami et al (2000); (4) Rodríguez-Gil et al (2005a); (5) this work; (6) Patterson et al (2003); (7) Thorstensen priv. com., & vsnetcampaign-dn 2681; (8) Kato et al (2002); (9) Tappert & Bianchini (2003); (10) Mennickent et al (2002); (11) Gänsicke et al (2000); (12) Fiedler et al (1997); (13) Billington et al (1996); (14) Shafter & Holland (2003).…”
Section: The Orbital Period Distribution Of Dwarf Novae In the Hqsmentioning
confidence: 99%